2020
DOI: 10.3390/jcm9051577
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Preemptive Transversus Abdominis Plane Block in Patients Undergoing Laparoscopic Colorectal Cancer Surgery

Abstract: Despite rapid advancements in laparoscopic surgical devices and techniques, pain remains a significant issue. We examined the efficacy of preemptive transversus abdominis plane (TAP) block for acute postoperative pain in patients undergoing laparoscopic colorectal cancer surgery. We retrospectively analyzed 153 patients who underwent laparoscopic colorectal cancer surgery with or without TAP block; among them, 142 were allocated to the TAP or non-TAP group. We performed between-group comparisons of demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Some clinical trials have demonstrated that several approaches to TAP block (lateral, subcostal, posterior) can successfully anesthetize the anterior or lateral abdominal walls by showing a reduction in postoperative pain and in opioid consumption after abdominal surgery. 1 , 2 , 9 Notwithstanding, there is some controversy about the effectivity of TAP block. Ghisi and Oh et al found that ultrasound-guided lateral TAP blocks do not reduce opioid consumption after total laparoscopic hysterectomy or laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical trials have demonstrated that several approaches to TAP block (lateral, subcostal, posterior) can successfully anesthetize the anterior or lateral abdominal walls by showing a reduction in postoperative pain and in opioid consumption after abdominal surgery. 1 , 2 , 9 Notwithstanding, there is some controversy about the effectivity of TAP block. Ghisi and Oh et al found that ultrasound-guided lateral TAP blocks do not reduce opioid consumption after total laparoscopic hysterectomy or laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 As the technique is simple and the target site is relatively easy to identify, this application has rapidly expanded to address anesthetic and analgesic needs in gastroenterology, obstetrics, and gynecology surgeries. [1][2][3] Despite the popularity of the technique, the extent of local anesthetic diffusion attributable to each approach remains unclear. [4][5][6] This uncertainty limits its use in upper and extensive abdominal surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…After extubation, patients were moved to the postoperative anesthesia care unit (PACU) where they received a further bolus of intravenous fentanyl at 0.5 µg/kg when the numeric rating scale (0 = no pain to 10 = absolutely intolerable pain) score was greater than 3. Postoperative opioids at the general ward included intravenous fentanyl, meperidine, or hydromorphone, as well as oral medications, including oxycodone and tapentadol [ 25 ]. Opioid administration was recorded by conversion to fentanyl units on postoperative days (PODs) 1, 3, and 5 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative opioids at the general ward included intravenous fentanyl, meperidine, or hydromorphone, as well as oral medications, including oxycodone and tapentadol [ 25 ]. Opioid administration was recorded by conversion to fentanyl units on postoperative days (PODs) 1, 3, and 5 [ 25 ]. Pain scores were recorded upon arrival at the PACU and at discharge from the PACU, as well as on PODs 1, 3, and 5.…”
Section: Methodsmentioning
confidence: 99%
“…Вступ. Проблема ефективного медикаментозного купірування больових відчуттів у післяопераційний період залишається актуальною у сучасній анестезіологічній та хірургічній практиці, зважаючи на те, що в результаті вираженого больового симптому після проведення хірургічних втручань відстрочується період мобілізації пацієнта, спостерігаються негативні клінічно-значимі зміни у низці органів та систем, а також знижується прогноз подальшої ефективної реабілітації з огляду на ризик розвитку потенційних ускладнень [1,2,3,4,5]. Крім того, вираженість больових відчуттів безпосередньо пов'язана і з вартісною складовою лікування, враховуючи потребу забезпечення пацієнта додатковими фармакологічними середниками та вимушене пролонговане його перебування в умовах стаціонару [6,7,8].…”
unclassified